Integration of wind power into an electricity system using pumped storage: Economic challenges and stakeholder impacts - Pejman Bahramian (Queen's University, Department of Economics, 2022)
The Province of Ontario has had an aggressive program of introducing wind electricity generation technologies into its generation supply mix. This, combined with the rigid baseload production by nuclear and hydro plants, has for 20 years created a surplus baseload electricity supply. Pumped hydro storage (PHS) is suggested as an economically viable technology for storing energy from non-dispatchable wind energy sources. An analytical framework has been developed to explore the feasibility of the PHS facility to manage the surplus supply of electricity and compare its cost performance with the alternative gas power plants. Two situations are analyzed. First, the PHS plant uses only surplus energy for the first 20 years of operation. Second, an additional 20 years of PHS usefulness is added by making investments in wind electricity generation to provide energy for pumping. Given the capital costs of building PHS in Ontario, the PHS expansion is not economically cost-effective for utilizing the projected off-peak surpluses. The economic analysis also illustrates that in the context of Ontario, the integration of PHS with wind power generation will have a negative impact on the Canadian economy in all circumstances. This loss is borne mainly by the electricity consumers of Ontario. Even considering the cost of CO2 emissions from a world perspective, this investment is not cost-effective. It would be much better socially from a world perspective and economically from Canada's perspective if the surplus baseload electricity from Ontario were given away free to the USA. It could then be used to reduce generation by natural gas plants in the USA, hence reducing CO2 emissions globally, without any incremental economic cost to Canada.
Keywords: O55; D61; Q42; 330; Economic analysis; Electricity; Ontario; Pumped hydro storage; Wind power